2021
DOI: 10.1007/s10823-021-09433-z
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion Among Official Language Minority Older Adults: A Rapid Review of the Literature in Canada, Finland and Wales

Abstract: It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Second, it is possible that older adults with high OTV speech quality tend to alienate the people around them who might otherwise be social connections, leading to higher levels of loneliness in high OTV older adult populations. This possibility would be consistent with previous findings that other limitations to verbal communication (e.g., linguistic barriers) are associated with higher loneliness in older adults and that older adults without family social systems tend to rely on casual socialization in public settings with other older adults for building social connection and support (Nyqvist et al, 2021; Torres, 2019). Finally, in keeping with the inhibitory deficit hypothesis (Arbuckle & Gold, 1993; D.…”
Section: Resultssupporting
confidence: 91%
“…Second, it is possible that older adults with high OTV speech quality tend to alienate the people around them who might otherwise be social connections, leading to higher levels of loneliness in high OTV older adult populations. This possibility would be consistent with previous findings that other limitations to verbal communication (e.g., linguistic barriers) are associated with higher loneliness in older adults and that older adults without family social systems tend to rely on casual socialization in public settings with other older adults for building social connection and support (Nyqvist et al, 2021; Torres, 2019). Finally, in keeping with the inhibitory deficit hypothesis (Arbuckle & Gold, 1993; D.…”
Section: Resultssupporting
confidence: 91%
“…Lower SES and education attainment were reported among the French-speaking minority outside Quebec 11 35. With these disadvantages, social adaptation to an environment where you do not speak the language of the majority can be challenging 12. Language barrier may cause isolation, difficulty in accessing services and health disparity 12 36.…”
Section: Discussionmentioning
confidence: 99%
“…With these disadvantages, social adaptation to an environment where you do not speak the language of the majority can be challenging 12. Language barrier may cause isolation, difficulty in accessing services and health disparity 12 36. Studies have reported that patients with language barriers were more likely to skip a follow-up medical appointment37 and less likely to adhere to treatment regimen 38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that official linguistic minority older adults encounter barriers and obstacles when seeking and receiving services in their own native language (Holmqvist & van Vaerenbergh 2013;Nyqvist et al 2021a). Additionally, differences in service quality as well as a lack of linguistic congruency in care services have commonly been experienced amongst official linguistic minority older adults in various contexts (Batista et al 2019;Guerin et al 2018;Martin et al 2018;Stout et al 2008).…”
Section: Introductionmentioning
confidence: 99%